2020
DOI: 10.33945/sami/ijabbr.2020.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperatures on germination and seedling growth of pyrethrum (Tanacetum cineraiifolium) under drought stress

Abstract: Pyrethrum is a perennial daisy grown commercially for the insecticide that is extracted from its flowers. In order to evaluate germination and seedling growth of pyrethrum under different temperature and drought stress treatments, the one year experiment was conducted in seed technology laboratory of Faculty of Agriculture of Islamic Azad University of Isfahan branch in 2018. During this experiment, polyethylene glycol (PEG) at 6 levels (0, -0.2, -0.4, -0.6, -0.8, -1.0 MP) and two temperature treatments (10 o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…2019). Germination percentage and seedling growth decrease with increasing stress level (drought) in Tanacetum cinerariifolium (Shahrajabian et al . 2020).…”
Section: Drought Stress and Crops Growth/productionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019). Germination percentage and seedling growth decrease with increasing stress level (drought) in Tanacetum cinerariifolium (Shahrajabian et al . 2020).…”
Section: Drought Stress and Crops Growth/productionmentioning
confidence: 99%
“…Germination and seedling vigour of Glycine max are affected by water stress, and these effects can be transmitted to the next generation (F 1 ) (Wijewardana et al 2019). Germination percentage and seedling growth decrease with increasing stress level (drought) in Tanacetum cinerariifolium (Shahrajabian et al 2020). Islam et al (2018 tested 100 genotypes of Oryza sativa under five levels of drought stress and observed that drought stress decreased germination by 6.6-95.8% with each increasing stress level.…”
Section: Drought Stress and Crops Growth/productionmentioning
confidence: 99%